Motivators and barriers to COVID-19 vaccination of healthcare workers in Latvia - Lielsvagere-Endele, Sintija; Kolesnikova, Jelena; Puzanova, Elina; Timofejeva, Svetlana; Millere, Inga (Frontiers in Psychology, 2022)
This study aims to identify motivators and barriers regarding Coronavirus disease 2019 (COVID-19) vaccination among Latvian healthcare workers (HCWs). Data were collected from March to May 2021 using an online survey. Overall, 1,444 participants took part in the study. From this pool of respondents, 528 indicated motivating factors in favor of the COVID-19 vaccination (86.5% were women; aged between 20 and 75 years), while 198 mentioned barriers against the COVID-19 vaccination (92.9% were women; aged between 19 and 68 years). The thematic analysis was conducted on two open-ended questions. The main motivators reported for COVID-19 vaccination were belief in the effectiveness of the vaccine, benefits of easing COVID-19 restrictions, responsibility, and restriction or pressure in case of non-vaccination. The main barriers reported regarding the COVID-19 vaccination were concerns about the effectiveness and safety of vaccines, perceived health risks of vaccination, risk perception toward COVID-19, misinformation about COVID-19 vaccines, belief that vaccination is being imposed, and belief in the conspiracy theories surrounding COVID-19. The results of this study help identify the existing motivating and hindering factors for COVID-19 vaccination among HCWs in Latvia. These results can be used to promote vaccination in HCW, develop information campaigns, and alleviate concerns of HCW.